The limits of criminological positivism: the movement for criminal law reform in the West, 1870-1940 - Pifferi, Michele (Routledge SOLON explorations in crime and criminal justice histories, 2022)
"The Limits of Criminological Positivism: The Movement for Criminal Law Reform in the West, 1870-1940 presents the first major study of the limits of criminological positivism in the West and establishes the subject as a field of interest.The volume will explore those limits and bring to life the resulting doctrinal, procedural and institutional compromises of the early 20th-century that might be said to have defined modern criminal justice administration.Written in a straight-forward and direct manner, this volume will be of great interest to academics and students researching historical criminology, philosophy, political science and legal history"--